EVALUATION OF THE INTEGRATION OF BIKE ROUTES TO THE RAIL TRANSPORT SYSTEM IN ZEYTINBURNU DISTRICT - Gulec Ozer, Derya; Yildirim, Ozge Ceylin; Uyduran, Hizir Gokhan; Turkkan, Dogan; Eyce, Nihat (MIDDLE EAST TECHNICAL UNIV, 2022)
The rapid change and transformation of socioeconomic activities in cities, the increase in the population, and the growth of the physical environment bring many problems. One of these problems is the increasing demand for transportation by the increased population. High demand for individual vehicles, traffic congestion, noise, air pollution, and environmental problems adversely affect urban accessibility, quality of life, and social health. Public transport has gained importance to provide access within the city, and other means of clean transportation should be integrated into this system. Bicycles have a high potential to be used as an alternative to individual vehicles on short and medium-distance journeys to ensure this integration into the transportation system. As a sustainable means of transportation, solutions such as bicycle rental systems, bicycle routes, and stations are planned to promote bicycle use and integrate into the rail transportation systems. The most crucial point is to plan bike routes and stations at the right spots and integrate them into the optimum level with the rail transport system. In the scope of this paper, a field study was carried out in the district of Zeytinburnu, Istanbul. IBB (Istanbul Metropolitan Municipality) bicycle rental system (Isbike) stations have been examined for integration with Marmaray, Metro, and Tramway stations. Therefore, Space Syntax analysis has been performed to determine the relevant bicycle routes. The study was created in three stages, (P1) the Space Syntax analysis is done with Open Street Map data on DepthMapX software, (P2) Bicycle routes are generated with the IBB railway transportation and Isbike station data, and (P3) Bicyclists experienced and evaluated these routes depending on physical, environmental and visual criteria via a survey. Finally, space syntax methods are used to analyze the physical structure of the city, and the integration of bicycle paths into the rail transportation system was evaluated; suggestions for urban planning for bikeability have been put forward.
Keywords: Space syntax; bikeability; Isbike; bicycle routes; Zeytinburnu; BUILT ENVIRONMENT; URBAN; NETWORK; CITIES; SPACE; Architecture